Políticas públicas de proteção ao patrimônio cultural e identidade: considerações acerca do título de patrimônio cultural da humanidade concedido à praça São Francisco, em São Cristóvão-Sergipe - Santos, Rosangela dos (2016)
The present work proposes to analyze the process of implementation of public policies for the protection of cultural heritage and its possible relation with the identity of the community of São Cristóvão-SE, considering that the starting point of the study is the concession to São Francisco Square of the title of Cultural Heritage of Humanity, occurred in the year 2010. In the course of the research, it was sought to identify the public actions that somehow involved aspects of the management of the cultural heritage listed and stimulation the identity of the population, that is, of the citizens. During the data collection, in the field, it was possible to apprehend elements related to the alienation of the population and to understand a fragile identity disconnected from the current context of the city. Denoting discontent with the current reality of the cultural heritage and little or no sense of identity; although public actions regarding the protection of the São Francisco Square were identified, as well as heritage education. Also as objective of the research were studied resources for a greater popular participation in the decisions about the protected cultural heritage; pointing out to the improvement of heritage education and shared management of São Francisco Square, which is in the process of being implemented and will contribute greatly to this scope. By conducting the interviews it was possible to capture people's perceptions about the implementation of such policies, obtain a social counterpoint to elucidate ways and approaches for the viability of the subject. It was used as methodology the application of semi-structured interviews to the population and public managers, using the Bardin content analysis method to perform the data exploration, as well as documentary research.